Tourist perception towards hygiene practices among foodservice establishments in Terengganu / Norazlina Rahmat, Norzaidah Ngali and Noralisa Ismail - Rahmat, Norazlina; Ngali, Norzaidah; Ismail, Noralisa (Research Management Institute (RMI), 2013)
The implication of food safety on tourism have been reported widely all around the world, but little information related to tourists’ experience in Malaysia can be found. Therefore, this research is carried out to determine tourist’s perception towards hygiene practices among food service establishment in Terengganu, Malaysia The data came from 550 self administered questionnaire. The responses to the questionnaire were measured by assigning hygiene perception points to each respondent according to their replies. The findings reveal that food and location were the most important hygiene factor that has been evaluated by the tourist while they dining in at food service establishment in the tourist attraction area. The findings also suggest that tourists’ perception of hygiene in the tourist attraction area around Terengganu was adequate and there was a need for training on the subject for better improvement in future.